การสื่อความหมายด้วยการสื่อสารเกี่ยวกับการสื่อสารในรายการโทรทัศน์ ทรู อะคาเดมี แฟนเทเซีย ฤดูกาลที่ 4 - ภุมรินทร์ แดงนุ้ย (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To find out the signification of metacommunication through the textual analysis of the reality TV program entitled "True Academy Fantasia Season 4" (AF4) which is the hybrid television genres between lives’ contenders ("Dream Pursuers") reality show and singing contest game show. The two main objectives of the research are (1) to analyze the process of metacommunication towards "Dream Pursuers" and (2) to find out the intended meanings of program messages and Dream Pursuers commuinicated through TV screen. The research finds that producers used 4 types of metacommunication intentionally and effectively. They are (1) metacommunication through TV cameras, (2) metacommunication through spoken words, (3) metacommunication through relationships among Dream Pursuers, and (4) metacommunication through SMS. Moreover, the researcher finds that the producers deliberately communicate the meanings of "Dream Pursuers" by presenting their individual characteristics, facial expressions, gestures, behaviors, singing, dancing and acting skills. Besides, the 4 types of metacommunication and the intended meanings of Dream Pursuers subtly encourage audiences to follow the program, become part of it, and cast their votes which result in the success of the program in terms of its popularity and income.